2013
DOI: 10.1111/ajt.12435
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Revascularization in Lung Transplant Recipients With Concomitant Coronary Artery Disease

Abstract: Coronary artery disease (CAD) is not uncommon among lung transplant candidates. Several small, single-center series have suggested that short-term outcomes are acceptable in selected patients who undergo coronary revascularization prior to, or concomitant with, lung transplantation. Our objective was to evaluate perioperative and intermediate-term outcomes in this patient population at our institution. We performed a retrospective, observational cohort analysis of 898 lung transplant recipients between 1997 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 31 publications
3
34
2
Order By: Relevance
“…We strive to correct risk factors for progression of CAD (diabetes mellitus, hypertension, and obesity) in all our recipients. We treat severe coronary artery disease in patients with no other disqualifying comorbidities with either pretransplant PCI or concurrent CABG at the time of transplant, if their left ventricular ejection fraction is normal and there is suitable coronary anatomy for revascularization ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We strive to correct risk factors for progression of CAD (diabetes mellitus, hypertension, and obesity) in all our recipients. We treat severe coronary artery disease in patients with no other disqualifying comorbidities with either pretransplant PCI or concurrent CABG at the time of transplant, if their left ventricular ejection fraction is normal and there is suitable coronary anatomy for revascularization ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have investigated the effects of CAD and coronary revascularization on lung transplantation outcomes ( 3, 5-8 ). Our study is the first one to investigate the impact of Mod-CAD on survival and morbidity after lung transplant by analyzing a large cohort of patients with a long-term, postoperative follow-up.…”
mentioning
confidence: 99%
“…In the case of BLTR, atherosclerotic diseases are potentially accelerated by immunosuppressive therapy (Kasiske, 1988;Hruban et al, 1990). Then, coronary artery diseases are not uncommon in BLTR (Reed et al, 2012;Castleberry et al, 2013).…”
Section: Cadenced Breathingmentioning
confidence: 99%
“…With increasing age, these patients may have additional comorbid disease burden, such as concomitant coronary artery disease requiring intervention. 17 Notably, a recent analysis confirmed that older IPF recipients with the higher functional status were more likely to benefit from receiving a BOLT but older IPF recipients with a reduced pre-operative functional status do not appear to derive similar benefit from BOLT. 18 Another report indicated that patients with IPF who are only listed for BOLT are less likely to receive a suitable organ and more likely to die on the waitlist.…”
Section: Discussionmentioning
confidence: 97%